Emergence of Relaxation Oscillations in Neurons Interacting With Non-stationary Ambient GABA - Adamchik, Denis A.; Matrosov, Valery V.; Kazantsev, Victor B. (Frontiers in Computational Neuroscience, 2018)
Dynamics of a homogeneous neural population interacting with active extracellular medium were considered. The corresponding mathematical model was tuned specifically to describe the behavior of interneurons with tonic GABA conductance under the action of non-stationary ambient GABA. The feedback provided by the GABA mediated transmembrane current enriched the repertoire of population activity by enabling the oscillatory behavior. This behavior appeared in the form of relaxation oscillations which can be considered as a specific type of brainwaves.